PENTINGNYA PELATIHAN DAN PENGEMBANGAN DALAM MENCIPTAKAN KINERJA KARYAWAN DI ERA DIGITAL - Wijaya, Shierli (ANALISIS, 2023)
In order to create the achievement of short-term and long-term goals in a company, a qualified workforce or employees is needed. With employees who have competence in their fields, it is expected that the company's ability to achieve its goals will also be better. One of the ways that companies do to maintain the quality of the performance of their employees is by holding training and development activities, especially in the digital era as it is today. Along with technological developments, companies need to adjust training and development methods that are suitable for employees. The development of digital technology is also a major requirement in the process of improving company management. For example, through webinar activities, training videos, to online training can be an option in implementing digital system learning. With digital employee training and development steps, the company can also indirectly save operational costs and this step is a practical way. The role of Human Resources as a workforce that will achieve company goals is expected to improve competitive strategies with more sophisticated technology so that employee performance can continue to increase. Keywords: Training, Development, Employee Performance